Are proton pump inhibitors better than histamine‐2 blockers for relieving symptoms of gastroesophageal reflux without esophagitis?. Issue 4 (April 2018) - Davidson, Jacelyn; Satre, Thomas
Abstract : EVIDENCE‐BASED ANSWER : Yes, proton pump inhibitors (PPIs) provide better relief of heartburn symptoms in patients without esophagitis than histamine‐2 blockers (SOR: A, meta‐analyses of RCTs). In patients with and without esophagitis, each individual PPI is estimated to be more effective than any histamine‐2 blocker for relief of gastroesophageal reflux symptoms, with omeprazole 40 mg daily showing the greatest efficacy (SOR: A, network meta‐analysis of RCTs).